LATEST TRENDS IN THE INDIAN VENTURE CAPITAL INDUSTRY AND THE USE OF WEBSITES BY FIRMS TO PRESENT NON-INDIVIDUALIZED INFORMATION - Kiran, Jai (2008)
Post liberalization, India has become one of the most sought after destination for investment by venture capital firms. Governments have been undertaking radical regulatory changes in order to provide finance for the developmental phase of their economies. The following study focuses on the importance of venture capital in India, its development and latest trends in the market. The analysis and data collection is on the basis of usage of websites to convey non-individualized information displayed by both Domestic and Foreign firms. A country that has always adapted to change has now developed a taste for Late-stage investments especially Management Buy-outs which is analyzed along with few case studies. This study also attempts to ascertain that Indian Venture Capital Market is no longer an infant.